(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
Aim: To verify the presence of Bolton ratios [Overall ratio & Anterior ratio] in Bangladeshi individuals with normal occlusion and class-I malocclusion. Methods:The materials comprised 120 pre-treatment study cast [60 male & 60 female aged 13-17 years] ,divided into two groups,first group were selected from the models of 60 students who had normal occlusion without crowding [equal male & female] and second group were selected from 60 patients who had Angle class-I crowding[equal male &famale], applied for orthodontic treatment based on the following criteria –permanent dentition from the 1st right molar to the 1st left molar and no interproximal caries or restorations.Bolton anterior & overallratios were performed for the study casts of the subjects using slide caliper. Results: The results showed that there was no significants differences between two groups .Also no significant gender differences were found in Bolton anterior& overall ratios. Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.24-28